FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK PERUSAHAAN MANUFAKTUR DI INDONESIA - Melita Anggraeni; Ferry Suhardjo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to examine the influence of firm size, return on assets, leverage, capital intensity, sales growth, composition of the independent board, firm age, and audit committee to tax avoidance. The population of this research is all manufactured companies listed in Indonesia a Stock Exchange from 2018 to 2020. Samples are obtained through purposive sampling method, in which samples that meet the sampling criteria in this research only 189 data form 63 manufactured companies listed in Indonesia a Stock Exchange from 2018 to 2020. This research used multiple regression method to test the effect of each variable in influencing to tax avoidance. The empirical result indicates that sales growth has influence to tax avoidance. However firm size, return on assets, leverage, capital intensity, composition of the independent board, firm age, and audit committee have no influence to tax avoidance.